Fit to belong: loneliness from the perspectives of adolescents from five European countries - Verity, Lily; Barreto, Manuela; Jefferson, Rebecca; , Fit to Belong Erasmus+ Project Team; Pinheiro, Adelaide; Seiroco, Ana Rita; Wroblewski, Dominik; Verseckas, Donatas; Aktas, Ilknur; Kupcinske, Indre; Aleksic, Jelena; Vinhas, Jorge; et al. (Frontiers in Education, 2023)
Previous qualitative research has explored how adolescents conceptualise loneliness, but, there is currently no examination of whether loneliness is understood differently by adolescents in different countries. To address that gap, the current study used semi-structured interviews to explore what loneliness is, and how to cope with it, from the perspectives of 29 adolescents (15 male, 14 female), aged 14–16 years from Lithuania (n = 6), Poland (n = 5), Portugal (n = 6), Serbia (n = 6), and Turkey (n = 6). Convenience sampling was used to recruit participants via project partners. Participants were included if they were aged 14–16 years, attended a school, youth centre, or foster home included in the Fit to Belong Erasmus+ Project, and did not have any disabilities or impairments that would impact their participation or understanding of the research activities. Thematic Framework Analysis (TFA) was used to analyse interviews with the adolescents and develop themes that reflected adolescents’ nuanced accounts of loneliness. Themes and subthemes described loneliness as a negative emotional experience involving a lack of belonging to one’s social environment and difficulty opening up to others. Themes recommended coping strategies for loneliness. Adolescents in the different countries described loneliness similarly: they understand it to involve negative emotions, and a lack of belongingness to one’s social environment, often due to social exclusion. Future research should explore the appropriateness of current measures and interventions that are used to address loneliness in youth and how those can be enhanced by including youth perspectives in the development process.